Maternal serum corticotrophin releasing hormone and ACTH levels as a predictive marker of uncomplicated preterm labor - Susan Abbas Abdul Al. Ammer (Genius Journals, 2023)
Numerous factors were looked into as preterm birth continues to be a key treatment issue.
Keywords: CRH; ACTH; Trichomonasiasis